Azathioprine and 6-thioguanine but not 6-mercaptopurine inhibit intra-macrophage replication of crohn's disease escherichia coli. (13th March 2011) - Knight, P; Campbell, B J; Rhodes, J M
Abstract : Introduction: Crohn's disease is associated with increased mucosal colonisation by E. coli that have an adherent, invasive phenotype that includes intracellular survival and replication within macrophages. Drugs that prevent this replication might have a therapeutic effect. We previously reported that azathioprine enhances bacterial killing by macrophages1 and therefore we evaluated the effect of its metabolites, namely 6-mercaptopurine and 6-thioguanine, at clinically relevant concentrations, on replication of E. coli within macrophages. Methods: Azathioprine metabolites, 6-mercaptopurine (4.2 × 10 −2 to 4.2 μM) and 6-thioguanine (8.2 × 10 −5 to 820 fmol/8×10 8 cells) were assessed for their effect on survival and replication of Crohn's E. coli isolate HM605 in J774-A1 macrophages in comparison to azathioprine (4.2 × 10 −12 to 4.2 μM). Macrophages were pre-treated with drugs for 24 h before bacterial infection. Cells were then infected with HM605 for 2 h to allow for internalisation. Extracellular bacteria were removed and killed with gentamicin (20 μg/mL) for 1 h. Macrophages were then either lysed (at 3 h) or parallel cultures incubated for a further 3 h in the presence of gentamicin (6 h). Internalised bacteria were enumerated by overnight growth on LB agar. Results: As previously seen, Crohn's E. coli HM605 significantly replicated within macrophages at 6 h compared to 3 h post-infection levels and azathioprine, at doses of 4.2 ×10 −9 to 4.2 μM, resulted in suppression of E. coli intramacrophage replication (all p<0.01, N=3–8) with a peak effect at 4.2 μM (0.33 fold replication relative to controls; p<0.001, N=5 Kruskal Wallis ANOVA). 6-thioguanine also suppressed E. coli replication in a dose dependent fashion with peak suppression at 82 fmol/8×10 8 cells (0.47 fold replication relative to control; p<0.001, N=4). However, 6-mercaptopurine did not suppress E. coli replication at any concentration tested. Conclusion: The enhancement of macrophage killing of intracellular E. coli by azathioprine and 6-thioguanine but not 6-mercaptopurine is intriguing. It might reflect the known ability of azathioprine but not 6-mercaptopurine to inhibit inducible nitric oxide synthase2 . The effect of 6-thioguanine on nitric oxide synthase has yet to be assessed. These effects of azathioprine and 6-thioguanine on bacterial killing by macrophages may be relevant to some of their therapeutic effects, perhaps particularly in fistulating Crohn's disease.